ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR CRUDE PALM OIL (CPO) DI PROVINSI SUMATERA UTARA - Sitepu, Indrawaty; Laura Butarbutar, Yenny (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine what factors influence CPO exports, institutions that play a role in CPO export activities, and the problems faced by CPO exporters in North Sumatra province. The research sample was determined purposively, namely PT. Socfindo. PT. Socfindo is one of the CPO exporters in North Sumatra province. The results of the study are as follows. First, the factors that have a partially significant effect on CPO exports in North Sumatra province include domestic CPO prices (X1), the Rupiah exchange rate against US (X3), the Rupee exchange rate against US (X4), and Indian GDP (X5 ) While the world price of CPO (X2) does not have a partial significant effect on CPO exports in North Sumatra province. Second, the institutions that play a role in CPO export activities in North Sumatra province include the Office of Industry and Trade, the Bank, the Belawan Agricultural Quarantine Center, the Entrepreneurs of Customs Services, the Sea Freight Expedition and the Belawan Port Customs. Third, the problems faced by CPO exporters include the imposition of high export tax, a long and complicated administration system, the timetable for sending CPO to importing countries is sometimes not timely, and the security is not optimal in Belawan Port